HYPERTENSION HEALTH EDUCATION AND HYPERTENSION EXERCISE TRAINING IN THE ELDERLY AT WISMA CEMPAKA UPT PSTW JEMBER - Rista Dwi Pratiwi; Intan Rahmawati; Resita Ovina Intiyaskanti; Nila Uli Saadah; Badrus Sholeh; Tantut Susanto (UNUSA Press, 2023)
The elderly are at higher risk of developing various degenerative diseases. Hypertension is often called the